“Where the time, silence and the voice of the churches live”: the Rome of Maria Kuncewiczowa - Prola, Dario (Poznańskie Studia Polonistyczne. Seria Literacka, 2020)
This paper is focused on a volume of short essays and notes by Maria Kuncewiczowa entitled Notatki włoskie. Przezrocza (Italian notes. Slides) from 1985. The first part is devoted to the evolution and the literary realizations of the Italian journey, starting from 1918, in order to offer an interpretation of the place occupied by Kuncewiczowa’s work in the panorama of contemporary Polish literature. In the second part, the author analyzes the genesis and genre of this literary text, recognizing its characteristics as a silva rerum, a traditional formal model of Polish literature which experienced renewed fortune in the second half of the twentieth century. The third part of the essay constitutes its thematic core: the author analyzes the image of Rome in all its many facets, relating it to the writer’s poetics and worldview.